Evolution and defragmentation of the vineyard landscape in the Rioja Alta (Spain) in the period 1956-2000 - I. Galilea; José Arnáez; Teodoro Lasanta Martínez; L. Ortigosa (Boletín de la Asociación de Geógrafos Españoles)
Texto resumen.